2020
DOI: 10.1111/ijcp.13494
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic measurements of the skin, fat and muscle in vitamin D deficiency

Abstract: Vitamin D is a steroid hormone which is essential for the calcium and phosphorus metabolism as well as the musculoskeletal system health. 1 Of note, its deficiency is related to various diseases and adverse outcomes. 2 Vitamin D is acquired from sunlight exposure, diet and various supplements. Although inadequate synthesis and intake are the main causes of vitamin D deficiency; body composition also affects the circulating vitamin D levels. In this sense, especially adiposity has a negative effect on the vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the presence of (for instance) decreased muscle tissue and increased adipose tissue, i.e., with no change in BMI, regional US evaluation will be important to reveal such a situation. Likewise, Ata et al [ 28 ] found an inverse relationship between VitD deficiency and trochanteric subcutaneous tissue thickness by using US. In this aspect, considering the concepts of sarcopenia and sarcopenic obesity in addition to VitD deficiency, the importance of regional US evaluation can be better understood [ 29 ].The use of US in dermatology allows more detailed examination of the skin [ 9 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of (for instance) decreased muscle tissue and increased adipose tissue, i.e., with no change in BMI, regional US evaluation will be important to reveal such a situation. Likewise, Ata et al [ 28 ] found an inverse relationship between VitD deficiency and trochanteric subcutaneous tissue thickness by using US. In this aspect, considering the concepts of sarcopenia and sarcopenic obesity in addition to VitD deficiency, the importance of regional US evaluation can be better understood [ 29 ].The use of US in dermatology allows more detailed examination of the skin [ 9 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our skin thicknesses were consistent with the literature [ 9 ], we found no difference between the groups. However, a preliminary study including 116 adults, skin thicknesses were found to be higher in the VitD deficient group [ 28 ]. Enrollment of more patients and detailed examination of clinical factors such as VitD usage and season are the superior aspects of our study.…”
Section: Discussionmentioning
confidence: 99%
“…It increases the absorption of calcium, and positively affects bone mineralization and muscle function (16). In addition, vitamin D is a steroid hormone whose importance is known especially for the structure and functions of the musculoskeletal system (17). In adults aged 65 and over, the endogenous synthesis of vitamin D is reduced by 25% compared to young adults (18).…”
Section: Introductionmentioning
confidence: 99%